Evaluation of a reliable non-invasive molecular test for the diagnosis of the causative agent of acute hepatopancreatic necrosis disease of shrimp - Jee Eun Han (Aquaculture Reports, 2017)
Acute hepatopancreatic necrosis disease (AHPND, also known as early mortality syndrome, EMS) has caused substantial mortality, up to 100%, in populations of penaeid shrimp cultured in SE Asia and in Latin America. The disease is caused by the bacterium Vibrio parahaemolyticus, which secretes binary toxins (PirAvp and PirBvp) resulting in the deterioration of the hepatopancreas tissue of infected shrimp. Diagnosis, screening, and monitoring of AHPND in shrimp populations involve sacrificing individuals to obtain tissue samples. This sampling method is undesirable when applied to valuable populations of broodstock. Here, we evaluated a non-invasive diagnostic method based on shrimp fecal samples that are analyzed by PCR. Small groups of Pacific white shrimp Penaeus vannamei were exposed to low levels of AHPND-bacteria and their feces were collected prior to any mortality observed (in the bioassays #1 and #2). Two protocols were evaluated. In one, DNA extracted from the fecal samples was directly analyzed by PCR. In the other, the fecal samples were cultured in TSB+ for 6 h to enrich the bacterial populations, then the enriched bacterial broth was used for PCR analyses. Our results showed that the presence of V. parahaemolyticus could be detected both in fecal DNA samples and in the enriched bacterial broth, but the bands from the bacterial broth showed stronger amplification than the DNA; 12 strong positive in the enriched bacterial broth, but only 7 strong positive in the fecal DNA samples. Also, the AHPND bacteria present in the feces is infectious, determined by a bioassay of feeding specific pathogen free indicator shrimp with AHPND-feces (in the bioassay #3), and this proves that the AHPND can be transmitted through a fecal-oral route.